Pengaruh Jumlah Penduduk Dan Produk Domestik Regional Bruto Terhadap Pembiayaan Bank Syari’ah Di Sumatera Utara - Nurul Jannah (Universitas Islam Negeri Sumatera Utara, 2018)
This study aims to determine whether there is a significant influence between population and gross regional domestic product on the financing of sharia banks in North Sumatra, and how much influence between the total population on the financing of sharia banks in North Sumatra and between gross regional domestic products. towards the financing of the Shariah bank in North Sumatra. The research design used is quantitative research design using techniques using multiple linear regression analysis techniques supported by classical assumptions and statistical tests with the help of SPSS 19 program. The sample of this study was the population, gross regional domestic product and the financing of the Shari'ah bank in North Sumatra from January 2009 to December 2011. The results showed that simultaneous gross regional population and gross domestic product had a significant and positive effect on bank financing. Shari'ah in North Sumatra. Partially, the more dominant factor that significantly affects the financing of the Shariah bank in North Sumatera is the factor of the population.